Konsep Pendidikan Anak Usia Dini - Toha Ma’sum (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
The character education of the children should be accomplished according to the characteristics of character education in early childhood, the values of the character in early childhood which include divine values, courage, honesty, sympathy, empathy, discipline, a sense of disciplinary nationalism, responsibility, courtesy, and courteous by using thematic approach which model of learning centered on children by using learning through three stages namely planning, implementation, and assessment. In its implementation, it must be supported by adequate facilities, long time, many media, and active children and also support of parents and human resources of educators and qualified personnel (if in non-family organizations).